Program Kuliah Kerja Nyata Pembelajaran Dan Pemberdayaan Masyarakat Kkn-Ppm : Pentingnya Menjaga Kesehatan Dengan Berolahraga - Ramadany, Weta; puspitasari, Mega; Oktasari, Teten; Pratama, Hendro Setia; Tranado, Hengky (Jurnal Gotong Royong, 2024)
Activities of the Community Empowerment Learning-Real Work Lecture Program (KKN-PPM). Real Work Lecture Activities (KKN) are field activities for students taking the final part of the Bachelor's/D4/Applied Bachelor's education program. This program In fact, it is mandatory for all students, because the university believes that this program is able to encourage student empathy and can contribute to solving problems in society. Pagar Gading Village has an area of ​​120 Ha, located in Pino Raya District, South Bengkulu Regency, with 339 heads of families and a population of 1.546 people. From the demographic data obtained with the number of elderly people numbering 187 people, the elderly exercise program carried out by Dehasen University KKN students is a good activity to maintain the health of the elderly in the village of Pagar Gading. when collecting data using primary data obtained from the results of questionnaires announced to the public and secondary data data obtained from the Pagar Gading Community Health Center. The method for evaluating the implementation of the Real Work Lecture (KKN) activity program is reviewed from the sustainability of the program's effectiveness, the sustainability of the program on the targets of each work program.